2012
DOI: 10.1590/s2179-64912012000100011
|View full text |Cite
|
Sign up to set email alerts
|

Análise da narrativa oral de pré-escolares antes e após estimulação de linguagem

Abstract: Both the reading of children's stories and the adult scaffolding contribute to the increase in the occurrence of events in autonomous narratives. There is no variation on the type of accountable/explicable conduct in the narratives. The internal state accountable/explicable conduct is predominantly used by preschoolers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
2
5
0
2
Order By: Relevance
“…This change suggests that the tutoring directs the attention of the students to the events of greater relevance, favoring the understanding of the story and the elaboration of the narrative. This finding is consistent with the study developed by Verzolla et al (23) , whose results showed that the effect of tutoring improves the quality of the narrative, since the children after tutoring increased the number of events narrated during the reevaluation. Therefore, tutoring is a sociolinguistic interaction that is effective in improving children's linguistics skills.…”
Section: Discussionsupporting
confidence: 93%
“…This change suggests that the tutoring directs the attention of the students to the events of greater relevance, favoring the understanding of the story and the elaboration of the narrative. This finding is consistent with the study developed by Verzolla et al (23) , whose results showed that the effect of tutoring improves the quality of the narrative, since the children after tutoring increased the number of events narrated during the reevaluation. Therefore, tutoring is a sociolinguistic interaction that is effective in improving children's linguistics skills.…”
Section: Discussionsupporting
confidence: 93%
“…Com relação ao segundo grupo de programas analisados, observa-se que o seu denominador comum reside no fato de que os quatro estudos se basearam na estratégia de leitura compartilhada e dialógica de livros infantis para o desenvolvimento de habilidades de letramento emergente. Três desses estudos tiveram como objetivo testar os efeitos dessa estratégia sobre habilidades linguísticas, como vocabulário (Fontes & Cardoso-Martins, 2004), compreensão oral (Borzone, 2005) e habilidades narrativas (Borzone, 2005;Verzolla et al, 2012), tendo os mesmos obtido resultados positivos, o que vai ao encontro dos dados da literatura (Lever & Sénéchal, 2011;Mol et al, 2008;Wasik et al, 2006).…”
Section: Discussionunclassified
“…Os estudos de Verzolla, Isotani e Perissinoto (2012) e de Borzone (2005) analisaram os efeitos da leitura compartilhada sobre as habilidades de linguagem oral de pré-escolares. O estudo de Verzolla et al (2012), realizado com 58 crianças com idade entre 5 e 6 anos, baseou-se num delineamento pré-experimental (pré-teste/intervenção/pósteste sem grupo controle), tendo como medida de resultado narrativas orais, produzidas a partir da visualização de cinco figuras compondo uma estória. A intervenção foi realizada pela pesquisadora, nas salas de aula, com grupos de 20 a 30 alunos, consistindo em 10 sessões semanais de 30 minutos, nas quais ocorria a leitura compartilhada de um livro por sessão.Os resultados indicam aumento significativo nas habilidades narrativas de eventos centrais.…”
Section: Programas Focados Na Linguagem Oral / Leitura Compartilhadaunclassified
“…According to the literature, the characteristics of the way parents talk to their children contribute positively to the composition of children's vocabulary (3) , and the more educated the parents, the richer the stimuli offered to the child (26) . In addition, the more children are stimulated in their environment, the greater the activation and access to vocabulary (27,28) . Although the socioeconomic status suggests physical and material resources that family may provide the child with, it is always necessary to jointly analyze other factors that can affect the vocabulary performance, such as environmental characteristics, the communicative interactions experienced, and the communicative style used by parents (5) .…”
Section: Discussionmentioning
confidence: 99%